Residential satisfaction analysis of developer products - Ari Septayuda; Yossyafra Yossyafra; Benny Hidayat (The International Journal of Politics and Sociology Research, 2022)
In housing with the type of commercial house, a CSI value of 78.80% is obtained, meaning that the residents of the housing are satisfied with the developer's product. The results of the analysis of the ISA method, there are 5 attributes that are a priority for improvement/improvement, namely (1) drainage system; (2) Quality of the roof, ceiling of the house; (3) Quality of house walls; (4) The quality of the floor of the house; (5) The quality of the frames, doors and windows of the house. In public housing, the CSI value is 64.25%, meaning that residents of the housing are quite satisfied with the developer's product. The results of the analysis of the ISA method. there are 8 attributes that are a priority for improvement/improvement, namely (1) Quality of sills, doors, windows of the house; (2) Provision of green open space; (3) Quality of house walls; (4) drainage system; (5) The quality of the floor of the house; (6)Public transportation at residential locations; (7) Residential environment security services; (8) The quality of the roof, the ceiling of the house.